Insect pathogens with special reference to pathogens of bark beetles (COL. Solytidae: Ips typographus L.) - Jurc, Maja (Zbornik gozdarstva in lesarstva, 2004)
This paper deals with the most important groups of insect pathogens, i.e. viruses, bacteria, fungi, nematodes and protozoans (microsporidia). We describe their basic characteristics, virulence, method of infecting or attackon the host, signs of illnesses in an affected host, pathogen survival in the outside environment, and the use of bioticcontrol of economically damaging insects. Particular importance is placed on bark beetle pathogens, which have been found in natural populations of hosts, particularly in the large spruce bark beetle (Scolytidae: Ips typographus L.). We also present ourexperience in studying entomopathogenic fungi on the species Dryocoetes autographus and Orthotomicus laricis in Slovenia.
Keywords: bolezni; disease; insekti; patogeni žuželk